Empathy-based marketing communication as a strategy to win the hearts of consumers during the covid-19 pandemic - Hadit Prasetyo, Sandika; Purnamasari, Oktaviana (Universitas Ahmad Dahlan, 2022)
The Covid-19 pandemic has affected many sectors including the economy. This situation forces companies to make significant changes in interacting with consumers through marketing communication activities. One of the marketing communication strategies used in pandemic situations is empathy-based marketing communication that promotes common interests and cares for others. This method aims to create a relationship, please help from all parties so that we can get through the difficult times of the pandemic together. Companies that have done this kind of thing include Burger King Indonesia, which carries out empathy-based marketing communications through the official Instagram account @burgerking.id. This study aims to determine the response of the Burger King Indonesia target audience, both user and non-user, regarding their empathy-based marketing communication efforts. This research approach is qualitative with the interview method. The data collection technique was carried out by interviewing 8 BurgerKing target audiences consisting of 4 users and 4 non-users. The results of the study show that the Burger King target audience positively welcomes Burger King's efforts in empathy-based marketing communications. The majority of informants admitted that they were touched by the message conveyed by Burger King. Not only that, they also admitted that Burger King's image was getting better, furthermore there were sources who even had the desire to make purchases and spread the message on their social media.